Analisis Kinerja Tata Kelola Teknologi Informasi pada Bank Menggunakan Framework Cobit 2019 - Kurniawansyah, Kevin; Marthiawati, Noneng; Rohayani, Hetty; Novitasari (Bulletin of Computer Science Research, 2023)
Jambi Province Regional Development Bank or Bank Jambi is a bank in Indonesia. This bank was founded on February 12 1959 and is domiciled in Jambi City. Jambi Regional Development Bank is one of the banks that faces competition from other banks. It expects the council to use the greatest capacity accessible, to win over the opposition. One of the assistance techniques to change the implementation of data innovation that takes advantage of business goals is data innovation administration. The acceptance of innovation administration using the COBIT 2019 structure will have a huge effect in supporting the goals of the organization on the grounds that legitimate data innovation administration can help the organization in competing with different opponents. Different improvements have occurred during the modern time frame like now and have fundamentally affected various parts of society, including the business and production areas of online stores. Taking advantage of this, processes that have been recognized as significant processes, such as APO08 (Managed Relationship), APO12 (Managed Risk), APO13 (Managed Security), DSS04 (Managed Continuity), and DSS05 (Managed Security Services), must be continues to be focused on achieving the significant standards that have been set. By focusing on this cycle and continuously assessing and improving, companies can achieve better goals in using data innovation offices for corporate achievements.